Development of Arabic Language Materials Using Lecture Maker Software in Universities - Salam, Muhammad Yusuf; Mudinilllah, Adam; Suharmon, Suharmon; Agustina, Annisa; Luksfinanto, Yovan (AT-TA'LIM, 2022)
Arabic material is the main goal for learning Arabic itself, but without the material, students can't be able to master the scope of Arabic courses. The teaching and learning process indeed uses teaching materials. Teaching materials must follow the times that are by the current trend, namely the era of 4.0, which must link information and communication technology in lectures. ICT is known as software, and hardware, which supports classes, is software. This software has various types, one of which is Lecture Maker. This study uses research and development or R D using the Borg and Gall model where the steps are as follows: a). Needs analysis, b). Design, c). Development, d) trials, e) revisions, f) dimensions, production, and distribution. With the development results, this teaching material is suitable for use in Arabic language courses in universities. It is also ideal for distribution because it can be applied to laptops or computers. After all, users do not need to install the Lecture Maker application itself.